Mitochondrial Cytochrome c Oxidase Defects Alter Cellular Homeostasis of Transition Metals - Brischigliaro, Michele; Badocco, Denis; Costa, Rodolfo; Viscomi, Carlo; Zeviani, Massimo; Pastore, Paolo; Fernández-Vizarra, Erika (Frontiers in Cell and Developmental Biology, 2022)
The redox activity of cytochrome c oxidase (COX), the terminal oxidase of the mitochondrial respiratory chain (MRC), depends on the incorporation of iron and copper into its catalytic centers. Many mitochondrial proteins have specific roles for the synthesis and delivery of metal-containing cofactors during COX biogenesis. In addition, a large set of different factors possess other molecular functions as chaperones or translocators that are also necessary for the correct maturation of these complexes. Pathological variants in genes encoding structural MRC subunits and these different assembly factors produce respiratory chain deficiency and lead to mitochondrial disease. COX deficiency in Drosophila melanogaster, induced by downregulated expression of three different assembly factors and one structural subunit, resulted in decreased copper content in the mitochondria accompanied by different degrees of increase in the cytosol. The disturbances in metal homeostasis were not limited only to copper, as some changes in the levels of cytosolic and/or mitochondrial iron, manganase and, especially, zinc were observed in several of the COX-deficient groups. The altered copper and zinc handling in the COX defective models resulted in a transcriptional response decreasing the expression of copper transporters and increasing the expression of metallothioneins. We conclude that COX deficiency is generally responsible for an altered mitochondrial and cellular homeostasis of transition metals, with variations depending on the origin of COX assembly defect.